Literacy and Numeracy in Crisis: A Phenomenological Study of Vocational High School Students in Central Java - Nia Sefiana; Rochman Hadi Mustofa (FKIP - Universitas Riau, 2026)
This study investigates the condition of literacy and numeracy skills among vocational high school students in Central Java, focusing on Surakarta, Sukoharjo, and Karanganyar. The research is motivated by national concerns regarding Indonesia’s low performance in international assessments and the critical role of literacy and numeracy in vocational education. The study aims to explore students’ lived experiences, contributing factors, and school responses related to literacy and numeracy challenges. A qualitative phenomenological approach was employed, with data collected through in-depth interviews, classroom observations, and document analysis involving students, classroom teachers, guidance and counseling teachers, and student affairs administrators. The findings indicate an imbalance between literacy and numeracy competencies, where numeracy shows gradual improvement while literacy remains a significant challenge, particularly in reading comprehension, analytical reasoning, and interpretation of long texts. These conditions are influenced by digital distractions, limited reading habits, weak learning foundations, and emotional factors such as low confidence and learning anxiety. The study concludes that strengthening literacy and numeracy in vocational education requires a holistic approach integrating humanistic pedagogy, contextual learning, responsible technology use, and collaborative support from schools and families.